CYBERBULLYING IMPACTS EDUCATION TO TACKLE DIGITAL SOCIAL CRISIS IN BUILDING AWARENESS AMONG TEENAGERS - Adi, Novi Hendri; Fernandes, Atman Lucky; Wahdi, Yera Wahda; Lubis, Muhammad Rizki Maulana; Husni, M Raihan; Siddiq, Raka Brama; Alamsyah, M Rizky; Sutejo; Yogi Ersan (Fakultas Ilmu Komputer, 2025)
Cyberbullying is an increasingly alarming social phenomenon in the digital era, especially among students. This community service aims to educate students about the forms, impacts, and prevention of cyberbullying. Through awareness sessions, participants showed improved understanding (11.72%), awareness of impacts (7.98%), and responsive attitudes (8.36%). These results indicate that the education program was effective in fostering awareness and readiness to address cyberbullying. The initiative also highlights the importance of collaboration between families, schools, and communities in building collective efforts to prevent and combat cyberbullying.